Construction of Humanistic Character thru IPM Extracurricular Programs: A Case Study at Muhammadiyah Yogyakarta High School - Rahayu, Anggraeni Putri; Masduki, Yusron; Waharjani, Waharjani; Sutarman, Sutarman (Early Publishing, 2026)
This research aims to examine the process and mechanisms of constructing students' humanistic character, including empathy, tolerance, and social concern, thru the extracurricular program of the Muhammadiyah Student Association (IPM) at SMA Muhammadiyah 3 Yogyakarta. The research uses a qualitative approach with a case study design to gain an in-depth understanding of the dynamics of value internalization within the context of student organizations. Data were collected thru participatory observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. The research results show that the construction of humanistic character occurs thru the integration of authentic social experiences, organizational deliberation mechanisms, participatory habituation, and the exemplary behavior of mentors and administrators. Empathy is constructed thru direct involvement in social activities; tolerance is formed thru deliberative practices and collective conflict resolution, while social concern is reinforced thru the equitable distribution of roles and responsibilities. These findings affirm that IPM functions as a space for the construction of contextual and sustainable humanistic values within the framework of progressive Islamic education.